Perspectivas ocupacionais de jovens com transtorno do espectro do autismo concluintes do ensino médio - Isabela Corrêa Borges (2023)
Autism Spectrum Disorder (ASD) is characterized by difficulty in social interaction, the presence of repetitive patterns of behavior and interest that affect the individual's functionality. The literature presents studies on the future perspectives of people with about intellectual disabilities, caregivers of people with ASD about their future, the familyexperiences of people with ASD and several studies with children. However, it is clear that the perspectives of youth with ASD themselves are not explored. This study aims to understand the occupational perspectives of youth with ASD after completing high school. This is a cross-sectional qualitative study, approved by the Human Research Ethics Committee, in which semi-structured interviews were carried out with five young people with ASD who were completing or who completed high school a year ago, aged between sixteen and eighteen years old, three males and two females, from different cities in the Southeast region of Brazil, in an online format by the Meet platform. The interviews underwent content analysis. Participants articulated occupational perspectives on study and work akin to young individuals with neurotypical development. Their aspirations included pursuing higher education and entering the workforce, but they expressed uncertainty regarding their choice of university courses. The perspectives presented are influenced by successful or unsuccessful school experiences, family support and maternal influence. In relation to romantic relationships, young people demonstrated insecurity and unpreparedness for relational skills, envisioning the beginning of dating relationships in the future. Access to these young people required a lot of time to approach the researcher and was marked by the presence of mothers as mediators to guarantee the safety and comfort of the participants, since the researcher was an unknown figure to the participants. These data reveal that students with ASD who manage to reach high school and, therefore, fit the profile of lower demand for support, are cognitively able to project continuity of studies and insertion into work, but present relationaldifficulties that make it difficult or prevent entry into different types of relationships.